Il lavoro dell’attore ovvero Elio e «la rappresentazione nascosta» - Schepis, Chiara (Mimesis Journal, 2017)
Laura Mariani, recreates in her essay the artistic career of Elio De Capitani who co-founded the Elfo teather of Milan in 1973. In fact, he performed four emblematic caracthers: Roy Cohn, Richard Nixon, Willy Loman and Mr. Berlusconi, the leads of the three examined acts and of the lm as well, precisely: Angels in America by Kushner, Forst/Nixon by Morgan, Morte di un commesso viaggiatore by Miller, Il Caimano directed by Nanni Moretti. The volume also includes interview to De Capitani and a rich gallery of scenic images.